RESPON BENIH KADALUARSA DAN LAMA PERENDAMAN TERHADAP PERTUMBUHAN JAGUNG MANIS (Zea mays Var. Saccharate L.) - Warsito Warsito; Hellina Rahmisari; Ardaniah Ardaniah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
This study aims to determine the effect of different varieties on the viability and early growth of expired sweet corn seeds (Zea Mays Var. Saccharate L.). The research was conducted using two varietal treatments, namely E1 (CMB Solid) and E2 (Pioneer P35). The parameters observed include germination rate, plant height, and root length at 7 and 14 days after planting (DAP). The data were analyzed using analysis of variance (ANOVA) followed by the BNT test at the 0.05 level.The research results show that the variety has a very significant effect on germination rate and early seedling growth. The CMB Solid (E1) variety yielded the best results with a germination rate of 0.28% at 7 days after sowing (DAS) and increased to 0.33% at 14 DAS, followed by better plant height growth and root length compared to the Pioneer P35 (E2) variety. This difference is due to the ability of each variety to maintain seed viability and vigor during storage. Based on the research results, it can be concluded that the CMB Solid variety is more tolerant of expired seed conditions and has a better ability to support seed germination and early plant growth compared to Pioneer P35.